You’re Part of Something Bigger: Macrorealist TV - Maynes-Aminzade, Liz (Romanticism and Victorianism on the Net, 2013)
“Dickensian” has become a buzzword in recent TV criticism not only because the term connotes a large character ensemble, but also because it connotes a diffuse ensemble. In TV series such as The Sopranos, The Wire, and Breaking Bad, many characters live and work so far apart from each other—whether in different neighborhoods of a city or different regions of the globe—that they fail to recognize how their actions affect each other. Through its wide spatial scope, this type of macroscopic “stranger narrative” explores a type of ethical confusion that is a byproduct of globalization. Namely, these narratives reveal to readers or viewers how they might be connected to and responsible for people they don’t even know.